Gamma-glutamyl transferase profile in various degrees of pruritus in cholestatic patients - Wahyu Usman, Baharuddin; Nu'man As Daud; Tutik Harjianti; Syakib Bakri; Andi Makbul Aman; Arifin Seweng (Acta Biomedica Atenei Parmensis, 2025)
Introduction: Cholestasis, a condition affecting liver function, can lead to complications like pruritus, fatigue, osteoporosis, hyperlipidemia, and steatorrhea. Pruritus is a presenting symptom in chronic cholestasis, often seen in intrahepatic disorders. It can impair life quality and be difficult to diagnose. Gamma-glutamyl transferase (GGT), a biomarker used to detect cholestasis, is linked to pruritus by inhibiting glutamine synthesis and stimulating glutamyl transferase. This study aims to determine the profile of GGT in cholestatic individuals with varying levels of pruritus. Methods: This cross-sectional observational study was conducted at RSUP Wahidin Sudirohusodo in Makassar and involved cholestatic patients diagnosed with chronic cholestasis. We collected demographic information, measured CGT levels in a lab prior to therapy, and used a 5D pruritus scale to measure pruritus. Data analysis was conducted using SPSS 26. Results: The study involved 78 participants, with a mean age of 53.8 ± 14.6 years. GGT values ranged from 15-784, and pruritus scale scores varied from 5-25. A significant negative correlation was found between GGT levels and pruritus scale scores (r = -0.510; p < 0.001). The mean GGT level was significantly lower in very severe pruritus (104.3) and greatest in moderate pruritus (356.9). Conclusion: This study concludes that greater levels of GGT correlate with reduced pruritus severity.